Health-related quality of life after camp-based family obesity treatment: an RCT - Beate Benestad; Tor-Ivar Karlsen; Milada Cvancarova Småstuen; Samira Lekhal; Jens Kristoffer Hertel; Silje Steinsbekk; Ronette L Kolotkin; Rønnaug Astri Ødegård; Jøran Hjelmesæth (BMJ Paediatrics Open)
Objective To compare the effects of a 2-year camp-based immersion family treatment for obesity with an outpatient family-based treatment for obesity on health-related quality of life (HRQoL) in two generations.Design Randomised controlled trial.Setting Rehabilitation clinic, tertiary care hospital and primary care.Patients Families with at least one child (7–12 years) and one parent, both with obesity.Interventions Summer camp for 2 weeks, with four repetition weekends, or lifestyle school, including four outpatient days over 4 weeks. Behavioural techniques to promote a healthier lifestyle.Main outcome measures Children’s and parents’ HRQoL were assessed using generic and obesity-specific measures. Outcomes were analysed using linear mixed models according to intention to treat, and multiple imputations were used for missing data.Results Ninety children (50% girls) with a mean (SD) age of 9.7 (1.2) years and body mass index 28.7 (3.9) kg/m2 were included in the analyses. Summer camp children had an estimated mean (95% CI) of 5.3 (0.4 to 10.1) points greater improvement in adiposity-specific HRQoL score at 2 years compared with the lifestyle school children, and this improvement was even larger in the parent proxy-report, where mean difference was 7.3 (95% CI 2.3 to 12.2). Corresponding effect sizes were 0.33 and 0.44. Generic HRQoL questionnaires revealed no significant differences between treatment groups in either children or parents from baseline to 2 years.Conclusions A 2-year family camp-based immersion obesity treatment programme had significantly larger effects on obesity-specific HRQoL in children’s self-report and parent proxy-reports in children with obesity compared with an outpatient family-based treatment programme.Trial registration number NCT01110096.